Faktor-Faktor Yang Berhubungan Dengan Kunjungan K4 Ibu Hamil Di Puskesmas Lubuk Buaya Tahun 2023 - Fonny Kurnia Putri (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
An antenatal care visit is a visit of a pregnant woman to a health worker as early as possible since she must trust her to get antenatal care services. An assesment of the implementation of antenatal care services can be done by looking at the coverage of K1 and K4. This study was conducted in Lubuk Buaya Primary Health Centre at december 28th 2022- February 20th2023 with a cross sectional design. Thirty nine sample was taken by total population technique to all pregnant women who give birth in Lubuk Buaya Primary Health Centre. Data was collected use questionnaire, processed data and analyzed by univariate and bivariate. Results of this study found 23.5% respondents did not have complete visit, 12.5% respondents had a low level of knowledge, 56.4% respondents have negative attitude, and 33.3% respondents did not have husband’s support. Statistical analysis shows correlation between complete visit (p<0.05) with knowledge (p=0.007) and husband’s support (p=0.039) and no correlation with attitude (p=0.052). We can conclude that there is a correlation between knowledge and family support with complete visit coverage. However, there is no correlation between attitude and complete visit.